National geographic kids. Everything robotics : all the robotic photos, facts, and fun! - Swanson, Jennifer; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2016)
They fix spacecraft, dance, tell jokes, and even clean your carpet! From the tiniest robo-bees to gigantic factory machines, robotics is all around you. This technology isn't just for science-fiction anymore -- it's real and more relevant than ever. With stunning visuals and energetic, impactful design, readers won't stop until they've learned everything there is to know about robotics.
Robots rule! -- Artificial life -- Robo-helpers -- Fun with robots -- Afterword: The evolving world of robotics -- An interactive glossary.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 8-12.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Robots -- Juvenile literature; Robotics -- Juvenile literature; Robots; Robotics; Robots -- Juvenile literature; Robotics; Robots; Electronic books- OSLIS; Juvenile works; Electronic books